Attachment and Mentalizing Abilities in Patients with Inflammatory Bowel Disease - Alessandro Agostini; Eleonora Scaioli; Andrea Belluzzi; Massimo Campieri (Gastroenterology Research and Practice)
Background. Inflammatory bowel diseases (IBD) are associated with stress, poor quality of life, and attachment insecurity. Mentalization is the human ability to perceive and reason about feelings and psychological dispositions of one’s self and others. The chronic disorders are believed to affect patients’ mentalizing abilities and to determine a shift towards attachment insecurity in patients affected. In this study, the attachment dimensions and mentalization were assessed in IBD patients and healthy controls. Further knowledge about the interplay among IBD, mentalization, and attachment might shed more light into the psychopathological mechanisms leading to insecurity and vulnerability to stress in IBD. Methods. A group of 96 IBD patients and 102 healthy controls completed the attachment style questionnaire (ASQ), the reflective functioning questionnaire (RFQ), and the Eyes test, a performance-based measure of mentalization. Results. Compared to controls, IBD patients have shown more pronounced attachment anxiety and lower scores in the Eyes test. Disease activity was negatively correlated with the Eyes test scores. Conclusion. These findings have suggested a plausible impact of IBD on mentalization abilities and have provided new insights into the interplay between IBD, deficits in mentalization, and attachment insecurity. IBD patients are highly vulnerable to disease-related stress that may promote impairments in mentalization. Low mentalization might play a central role in the development of attachment insecurity and emotional disturbances in IBD. The present study’s results might open new scenarios for psychodynamic approaches to the treatment of the emotional disturbances in IBD based on attachment and mentalization theory.